Survival rate after paraquat poisoning: impact of emergency clinical and laboratory variables - Laurindo Pereira de Souza; Rafael Ayres Romanholo; Cidia Vasconcellos (Rev Rene)
Objective: to analyze the association of survival to emergency care measures, clinical symptoms and biochemical markers used for paraquat intoxicated patients. Methods: retrospective cohort, guided by the Strengthening the Reporting of Observational Studies in Epidemiology tool. The data collection and analysis protocol were based on two phases: first, with the survey of the investigation forms of exogenous poisoning from the Secretariat of Epidemiological Surveillance; second, with the analysis of information in printed medical records. Results: of the 36 (100%) patients investigated, 19 (53.0%) survived; regarding the clinical manifestations, there was statistical significance for the respiratory system (p=0.003); regarding the biochemical variables, there was statistical significance for liver enzymes. The initial emergency measures 13(56.5%) of survivors received gastric lavage with activated charcoal. Conclusion: we observed a lack of efficacy of the impacts of emergency care measures and medications in increasing patient survival.